Job security of occupational physicians - Elbir, Nazli (Annals of Medical Research, 2021)
Aim: This article discusses the function of occupational physicians in relation to their preventive role in occupational health and the significance of maintaining their professional independence. Material and Methods: The study examines Code no. 6331, the basis of Turkish occupational health and safety legislation and the Regulation on Occupational Physicians’ and Other Healthcare Professionals’ Duties, Powers, Liabilities and Training, which constitutes a regulatory framework for the occupational healthcare services. Amendments made to these texts will be evaluated in the context of the need for professional independence for occupational physicians. Results: Amendments made in 2015 to occupational health and safety legislation benefit occupational physicians by subjecting employers to pay indemnity in case of termination of contract or causing a disadvantage for the physicians. Conclusion: Amendments made in 2015 have been criticized in legal doctrine and by Turkish Medical Association for not providing full job security to occupational physicians. It is recommended that a special job security regulation similar to the one that trade union representatives have, be granted to occupational physicians. Another recommendation is, subjecting the termination of contracts of occupational physicians to the approval of administrative authorities such as labor inspectors.
Keywords: Occupational physician; occupational health and safety; occupational health and safety services